Increasing Parental Knowledge About Child Feeding: Evaluation of the Effect of Public Health Policy Communication Media in France - De Rosso, Sofia; Ducrot, Pauline; Chabanet, Claire; Nicklaus, Sophie; Schwartz, Camille (Frontiers in Public Health, 2022)
Background: Unhealthy eating behaviors are risk factors for noncommunicable diseases. Parents largely influence the development of eating behaviors during childhood through their feeding practices. Parental feeding practices in line with recommendations are more likely to turn into healthier outcomes in children. From a public health perspective, it should be first ascertained whether providing parents with recommendations about child feeding is a useful approach for increase parental knowledge. Recently, the French health authorities developed a brochure covering updated child feeding recommendations. The present study aims to evaluate the short-term effects of reading this brochure on parental knowledge about child feeding, distinguishing knowledge accuracy and certainty. Methods: A brochure containing updated child feeding recommendations for 0-3 years old was developed by the French public health agency. A representative sample of French parents (n=400) was targeted to complete an online questionnaire (T0) comprising 30 statements regarding child feeding. For each statement, parents indicated whether it was true/false and how certain they were of their answer (4-point scale). After receiving and reading the brochure, the same parents completed the same questionnaire three weeks later (T1). Accuracy (number of correct answers) and certainty (number of mastered answers: correct answers given with the maximal degree of certainty) were compared at T1 vs. T0 using paired t-tests. Knowledge evolution based on parental age, parity and education level was tested with linear models. Results: A total of 452 parents responded at T0 and T1 and were considered for analysis. Between T0 and T1, the number of correct answers (median 22 to 25, t(451)=17.2, p=<0.001) and mastered answers (median 11 to 17, t(451)=18.8, p=<0.001) significantly increased. The median of the difference between T1 and T0 was larger for mastered than for correct answers. The observed evolution in knowledge was independent of parental age, parity or education level. Conclusions: A brochure containing child feeding recommendations has the potential to increase the accuracy and, to an even greater degree, the certainty of parental knowledge. This increase was observed even for younger or less educated parents.